Effect of erythromycin residuals in food on the development of resistance in Streptococcus pneumoniae: an in vivo study in Galleria mellonella - Baranchyk, Yuliia; Gestels, Zina; Van den Bossche, Dorien; Abdellati, Saïd; Britto Xavier, Basil; Manoharan-Basil, Sheeba Santhini; Kenyon, Chris (PeerJ, 2024)
Background The use of antimicrobials to treat food animals may result in antimicrobial residues in foodstuffs of animal origin. The European Medicines Association (EMA) and World Health Organization (WHO) define safe antimicrobial concentrations in food based on acceptable daily intakes (ADIs). It is unknown if ADI doses of antimicrobials in food could influence the antimicrobial susceptibility of human-associated bacteria. Objectives This aim of this study was to evaluate if the consumption of ADI doses of erythromycin could select for erythromycin resistance in a Galleria mellonella model of Streptococcus pneumoniae infection. Methods A chronic model of S. pneumoniae infection in G. mellonella larvae was used for the experiment. Inoculation of larvae with S. pneumoniae was followed by injections of erythromycin ADI doses (0.0875 and 0.012 μg/ml according to EMA and WHO, respectively). Isolation of S. pneumoniae colonies was then performed on selective agar plates. Minimum inhibitory concentrations (MICs) of resistant colonies were measured, and whole genome sequencing (WGS) was performed followed by variant calling to determine the genetic modifications. Results Exposure to single doses of both EMA and WHO ADI doses of erythromycin resulted in the emergence of erythromycin resistance in S. pneumoniae. Emergent resistance to erythromycin was associated with a mutation in rplA, which codes for the L1 ribosomal protein and has been linked to macrolide resistance in previous studies. Conclusion In our in vivo model, even single doses of erythromycin that are classified as acceptable by the WHO and EMA induced significant increases in erythromycin MICs in S. pneumoniae. These results suggest the need to include the induction of antimicrobial resistance (AMR) as a significant criterion for determining ADIs.
Keywords: Streptococcus pneumoniae; Acceptable daily intake; AMR; Minimum selection concentration